The Design of "KIDOS" (Knowledge Information Domain System) in Education Management System - Kainde, Quido C.; Sumual, Herry; Rawis, Joulanda A M; Tambingon, Henny Nikolin; Palilingan, Rolles N.; Umbase, Ruth; Lumapow, Harol R.; Ratu, Donal (International Journal of Information Technology and Education, 2025)
This research aims to design and implement KIDOS (Knowledge Information Domain System) as an innovative solution within the educational management system in North Sulawesi Province. KIDOS is an advancement of the Education Management Information System (EMIS), utilizing artificial intelligence (AI) and text mining technologies. Specifically, the system is designed to manage qualitative knowledge from school principals through analysis of best practice essays, mapped against the 14 Principles of Educational Management. KIDOS provides a digital platform for principals to document and share best practices and delivers automated feedback, sentiment analysis, and actionable managerial recommendations. The research methods included system design, functional testing, and evaluation using the IS Success Model and Technology Acceptance Model (TAM). The results indicate that KIDOS operates effectively, is well-accepted by users, and provides strategic insights for educational policy-making. The system is expected to strengthen data- and knowledge-based management practices and serve as a model for AI-based EMIS development in other regions. KIDOS demonstrates the importance of adaptive and contextual digital transformation in improving the quality of education services.